Pengaruh Gaya Hidup, Promosi, dan Lokasi terhadap Perilaku Konsumen Kedai Kopi di Kota Batam - Deviana Deviana; Realize Realize (Universitas Batanghari Jambi, 2023)
The impact of globalization has made coffee shop business owners continue to innovate so that their business can survive with increasingly fierce competition. Several factors such as giving attractive promotions and competing to find the most appropriate location that can attract consumers. With the spread of franchise coffee shops in Batam, non-franchise coffee shop business owners must start analyzing coffee shop business strategies with existing consumer behaviour so they don't lose out in this industry. The purpose of this experimentation is to understand if there is a connection between lifestyle, promotion and location towards coffee shop consumer behaviour in Batam Island. The experimentation is a quantitative research in which author gathers information by spreading questionnaires to franchised coffee consumer in Batam island. The sample collection technique that has been used is simple random sampling and done by using multiple regression analysis. Through the experiment and the analysis from 385 respondents, the results indicate that there is significant influence between lifestyle towards consumer behaviour, there is significant influence between promotion and consumer behaviour and there is no influence between location and consumer behaviour significantly. Different result shows with three variables involves with consumer behaviours where there is significant influence worth 32.3%. But simultaneously, lifestyle, promotion, and location influence consumer behaviour by 62.02.